Melt‐Extruded Sensory Fibers for Electronic Textiles. Issue 3 (14th March 2022) - Tabor, Jordan; Thompson, Brendan; Agcayazi, Talha; Bozkurt, Alper; Ghosh, Tushar K.
Abstract : Inside Cover : Fiber‐based sensors are critical to the development of electronic textiles. In article number 2100737, Tushar K. Ghosh and co‐workers present a practical and scalable method of producing textile‐based sensory fibers using the commonly used commercial melt extrusion method. Once assembled into the fabric, the fibers can act as a multimodal sensory array. The woven substrate can detect the location and level of applied pressure, thereby illustrating its potential use as a sensor in textile structures.